Night eating syndrome with morbid obesity and dysthymia: A case report - A psychobiological approach - Ainsah O,; Osman CB, (Penerbit UKM, 2007)
The traditional physical and cosmetic-centered model without paying serious attention on the underlying psychosocial issues of care are ill suited to successful treatment outcome of obesity. The objective of this article is to report a case of a retired Malay army sergeant who presented with night eating syndrome (NES) with morbid obesity and dysthymia, and to discuss the psychobiological aspect of the case including to evaluate the effectiveness of the combination treatment of pharmacotherapy and cognitive behavior therapy alongwith diet counseling. The diagnosis was made by using the Structured Clinical Interview Diagnosis (SCID) for DSM-III-R diagnosis and the severity of depression was assessed by Hamilton Depressive Rating Scale. The patient’s body mass index was 45, He was found to have dysthymia and the Hamilton Depressive Rating Scale score was 13. We found that the combination of pharmacotherapy, cognitive behavior therapy and nutritional education with the help of the physician proved to be effective in treating morbid obesity with NES and Dysthymia